Historical overview of the Barmen Theological Declaration of 1934 - Krötke, W (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This article places the Barmen Theological Declaration against the backdrop of nationalist socialist rule and the way it was supported by the so-called “faith movement” of the “German Christians”. Reference is also made to the resistance to it by the “Confessing Church.” The fact that the six theses of Barmen (as “Protestant truths”) follow the style of a reformatory confession is reiterated, but it is also argued that confessions always need to be tested in the light of Scripture, hence the need for the church of Jesus Christ, as church in the world, to go “with Barmen and beyond Barmen.” The article also refers to the interpretation history of the phrase “the one Word of God” in the famous first thesis of Barmen. In the last section four cursory remarks are made about the possible enduring implications of the Barmen Declaration. It is emphasised that freedom serves as a keyword in the Declaration, expressing the special profile of the church of Jesus Christ.